Lensless Fourier-Transform Terahertz Digital Holography for Full-Field Reflective Imaging - Zhang, Yaya; Zhao, Jie; Wang, Dayong; Li, Kunlun; Rong, Lu; Wang, Yunxin (Frontiers in Physics, 2022)
Continuous-wave terahertz digital holography (TDH) is a full-field lensless phase imaging approach usually with the coherent THz laser. It has the potential to be applied to nondestructive testing. In order to simplify the reconstruction and utilize the THz radiation with higher efficiency, a full-field reflective lensless Fourier-transform TDH (RLF-TDH) configuration is proposed with oblique illumination mode based on 2.52 THz radiation. A spherical reference beam is generated by a reflective concave mirror in order to reduce the loss of THz radiation, which is different from other configurations of the same kind. In the reconstruction process, the complex-amplitude image can be obtained by directly applying single Fourier transform to the digital hologram. A tilted plane correction method is implemented to correct the anamorphism caused by the non-parallel planes between the object and recording plane. The profile information of the object can be measured from the unwrapped, aberration-free phase image. Two reflective gold-coated samples are adopted to demonstrate the validity of the RLF-TDH imaging system.